Presupposition in Kamala Harris’ Statements in the 2024 United States Presidential Debate - Fahriza, Muhammad; Ruminda, Ruminda; Wardoyo, Cipto (Journal of English Language and Education, 2025)
Debate is basically an exchange of opinions on a subject by giving reasons to defend each other's ideas. In the election context, debates are often related to social, political, and economic issues to gain audience votes. The purpose of this study is to explore what presuppositions were used by Harris in the 2024 U.S. presidential debate. The researcher used a qualitative methodology and presented the results descriptively. The results found that there were 16 existential, 45 factive, 8 lexical, 5 structural, 3 non-factive, and 0 counter-factual presuppositions. Based on these findings, the researcher concludes that Harris, in the debate against Trump, used concrete sentences that contain facts. This shows that Harris influenced the audience using assumptions that could not be directly refuted by the voters.